EFFICIENCY AND SUSTAINABILITY OF LIFEBANK MICROFINANCING PROGRAM IN PANAY ISLAND - Impenido, Lady Lyn F. (IDEAS: Journal of Management & Technology, 2024)
Sustaining the role of microfinance in the development of the economy is vital in supplementingthe needs of marginalized population. LifeBank Microfinance can help fund sustainablelivelihood programs. The study was conducted to determine the level of efficiency and degreeof sustainability of LifeBank Microfinancing program in Panay Island for the year 2023.Usingdescriptive-correlational research design, the study utilized 226 respondents employed at theinstitution as of August 2023. A validated and reliability tested researcher-made questionnairewas used to gather the needed data from randomly selected respondents. Statistical tools usedto analyse and interpret the data were frequency count, percentage, mean, t-test, analysis ofvariance, and Pearson r. The findings of the study revealed that respondents themselvesobserved a high level of efficiency in terms of management technique, loan system, andmarketing approaches. Likewise, the overall sustainability shows a high degree respectively inrepayment rate, operating cost, and market interest rate. There was no significant differencefound in the level of efficiency when respondents were grouped according to their age, sex, andemployee category. In the degree of sustainability, no significant difference where found whenthe respondents were grouped according to age and employee category. However, significantdifference was found when they were grouped according to sex. Generally, the level ofefficiency and the degree of sustainability are mutually dependent. Thus, the higher theefficiency, the higher the degree of sustainability. This implies that it is not only the businessworld that is transforming, but the human resources as well. A culture of sustainability caninfluence how employees behave and can affect the sustainability of the business as whole. Thisalso implies that employees’ efficiency level in LifeBank Microfinancing Program in PanayIsland is using efficient management techniques, implementing a well-structured loan system,and adopting strategic marketing approaches for the success and growth of the organization.Moreoever, it can be noted that LBRB can further ensure the long term sustainability of itsoperations by having a monitoring or careful examination on repayment rate by assessing theability of borrowers to meet their financial obligations.